Bone regeneration after traumatic skull injury in Xenopus tropicalis. (December 2018) - Muñoz, David; Castillo, Héctor; Henríquez, Juan Pablo; Marcellini, Sylvain
Abstract: The main purpose of regenerative biology is to improve human health by exploiting cellular and molecular mechanisms favoring tissue repair. In recent years, non-mammalian vertebrates have emerged as powerful model organisms to tackle the problem of tissue regeneration. Here, we analyze the process of bone repair in metamorphosing Xenopus tropicalis tadpoles subjected to traumatic skull injury. Five days after skull perforation, a dense and highly vascularized mesenchymal is apparent over the injury site. Using an in vivo bone staining procedure based on independent pulses of Alizarin red and Calcein green, we show that the deposition of new bone matrix completely closes the wound in 15 days. The absence of cartilage implies that bone repair follows an intramembranous ossification route. Collagen second harmonic imaging reveals that while a well-organized lamellar type of bone is deposited during development, a woven type of bone is produced during the early-phase of the regeneration process. Osteoblasts lying against the regenerating bone robustly express fibrillar collagen 1a1, SPARC and Dlx5 . These analyses establish Xenopus tropicalis as a new model system to improve traumatic skull injury recovery. Highlights: A novel traumatic skull injury assay was implemented in Xenopus tropicalis tadpoles and froglets. A dense and highly irrigated mesenchymal plug forms over the wound in 5 days. A woven type of bone closes the lesion in 15 days, and subsequently converts into lamellar bone. Bone repair occurs in the absence of cartilage. Osteoblasts involved in regeneration robustly express Collagen 1a1, SPARC and Dlx5 transcripts.